An in-house centrifugation and membrane filtration technique for identifying microorganisms from positive blood culture bottles with high identification rates using matrix-assisted laser desorption ionization–Time-of-flight mass spectrometry: A preliminary report. Issue 3 (March 2020) - Tsuchida, Sachio; Murata, Syota; Miyabe, Akiko; Satoh, Mamoru; Takiwaki, Masaki; Matsushita, Kazuyuki; Nomura, Fumio
Abstract: Matrix-assisted laser desorption ionization–time-of-flight mass spectrometry (MALDI-TOF MS) is one of the most promising technologies for the identification of microbial pathogens directly from positive blood culture bottles. As blood culture bottle medium contains various nonbacterial proteins, including those derived from blood cells, pretreatment to effectively remove host cells is key for successful proteome-based identification of microorganisms. Although the Sepsityper® kit is the most widely used pretreatment protocol, its performance is not satisfactory, particularly for gram-positive isolates. We developed a new in-house protocol, the centrifugation and membrane filtration technique (CMFT), in which vacuum-filtration is coupled with differential centrifugation. We prospectively evaluated the performance of this novel method compared with that of the Sepsityper®. For gram-negative bacterial isolates, the species-level identification rates obtained with the CMFT and the Sepsityper® were comparable (98.8% vs 92.9%). By contrast, for gram-positive isolates, the performance of the CMFT was significantly better than that of the Sepsityper® ( P < 0.05). Using our new protocol, 81 (95.3%) isolates were identified with a score >2.0, and 85 (100%) isolates were identified with a score >1.7, versus 46 (54.1%) and 69 (81.2%), respectively, for the Sepsityper®. These results are preliminary, but considering that this novel protocol provides notably high species-level identification rates for gram-positive isolates, it deserves assessment in a larger-scale study with a variety of platforms for MS-based identification of microorganisms.